Experience with sulphamethoxazole (SMZ)/trimethoprim (TMP) combination in purulent meningitis not responding to conventional microbial therapy - Sumarmo Sumarmo; Mugiyo K.; Mandoyono Mandoyono; Lauritha S. P.; Adji Suntoro (Indonesian Pediatric Society, 1981)
Tell infants ranging in age from two days to nine months with purulent meningitis who were considered therapeutic failures after conventional microbial therapy (i.e. ampicillin, chloramphenicol, gentamicin, amikin, cloxacillin in any combination) were included in this study. A solution consisting of SMZ 80 mg/mL and TMP 16 mg/mL in propylene glycol (Bactrilll, Hoffman-La Roche A.G. Basle/Switzerland) was given intravenously to the patients. The daily dose was 10 mg/kg BW TMP/24 hours for the first three days followed by 6 mg/kg BW TMP/24 hours divided in two doses given intravenously every 12 hours.Nine patients recovered, 7 of them rapidly within 10 - 21 days after SMZ/TMP administration and the other 2 patients within 27 and 33 days respectively. One infant improved but died afterwards of complicatIons not related to the treatment.No hematological nor cutaneous and gastrointestinal side effects were observed. The liver and renal function test performed on 3 out of 10 cases on the first few days of the commencement of treatment and 3 weeks later, were all within normal limits.Our experience with the use of parenteral SMZ/TMP in infants with bacterial meningitis not responding to conventional microbial therapy gave encouraging results.